Implementering av Långsiktigt hållbar dagvattenhantering i kommunal planering i Bottenvikens vattendistrikt : Hinder och förutsättningar - Mikkola Bouvin, Johanna (Umeå universitet, Institutionen för geografi, 2021)
One of the challenges today ́s planners face with the urbanization is how to adapt the city to the climate changes, with the increasing precipitation that causes flooding. The concept of Sustainable stormwater management aims to prevent flooding and ensure good water quality, which complies with the EU Water Framework Directive. The aim of this thesis is to investigate how Sustainable stormwater management and climate adaption is implemented in municipal planning in the Bothnian Bay Water District and to map the prevailing conditions and obstacles that may occur. Semi-structured interviews were conducted with municipal planners in Luleå, Umeå, Haparanda, Kiruna, Boden, Piteå and Skellefteå. The answers were analyzed using a deductive thematic analysis method. The interview answers were coded at different levels with the research questions as a focus. This resulted in main themes and subcategories. The result shows that five of seven interviewed municipalities are in the process of implementing Sustainable stormwater management. The municipalities are aware of pollution in stormwater and the importance of good water quality, the goal is to achieve a natural flow of stormwater. Most of the municipalities work with the stormwater issue across administrative boundaries in collaboration. The climate adaptation work in the municipalities consists mainly of rainfall mapping and elevation of buildings. The greatest obstacles to the implementation are unclear division of responsibilities, lack of resources and knowledge and the question of land use. Regarding the municipality's size and geographical locations, factors such as terrain, watercourses / recipients, demographics, finances and human resources are of importance. En av utmaningarna som urbaniseringen för med sig och som dagens planerare måste hantera är hur staden ska anpassas till klimatförändringarna; med den ökande nederbörden som orsakar översvämningar. Konceptet Långsiktigt hållbar dagvattenhantering syftar till att förhindra översvämningar och ...